A novel technique for prevention of gastroesophageal reflux in staged repair of long gap esophageal atresia with tracheoesophageal fistula - Vipul Prakash Bothara; Gyan Prakash Singh; Shiv Narain Kureel (Wolters Kluwer Medknow Publications, 2020)
Aim: The objective of the study is to report a novel technique of preventing gastroesophageal reflux and air leak from fistula to stomach in patients of tracheoesophageal fistula with long gap atresia, to buy time for the staged procedure. Methods: Seven patients of tracheoesophageal fistula with upper pouch of esophagus at 2nd thoracic vertebra were selected for the staged procedure. Weight ranged from 1.7 to 1.8 kg. During the 1st stage surgery for gastrostomy, midline strip of linea alba attached to xiphoid process was harvested and slinged around the gastroesophageal junction, along with right cervical esophagostomy. After radio-nuclear scan, the demonstration of abolition of gastroesophageal reflux, gastrostomy feed was started. The 2nd stage surgery performed after 6 weeks, included mobilization of esophagostomy, release of sling, thoracotomy, and tension-free esophageal anastomosis. Outcome measurement includes (1) prevention of air leak from esophagus into the stomach, (2) abolition of gastroesophageal reflux, (3) ability to start gastrostomy feeds, and (4) reversal of occlusion after release of the sling. Results: The placement of linea alba sling and elevation of gastroesophageal junction, abolished air leak from fistula to stomach in all. Radio nuclear scan demonstrated abolition of gastroesophageal reflux in 6 with weight gain after gastrostomy feeding. One patient expired due to sepsis. One patient underwent final repair with reversal of occlusion with release of the sling. Conclusion: Using a sling of the linea alba around the cardioesophageal junction, prevents gastroesophageal reflux and escape of air from esophagus into the stomach, gives time to improve the respiratory and nutritional status of the patient, for a subsequent safer delayed primary anastomosis.